International Financial Reporting Standard Adoption and Value Relevance of Accounting Information of Listed Deposit Money Banks in Nigeria - Ibrahim Mallam Fali; Kwabena Ampong; Adebola Abass Jabar; Agana Ogagaoghene John (International Journal of Business Economics (IJBE), 2023)
The study examined the effect of International Financial Reporting Standard (IFRS) adoption on value relevance of accounting information of listed deposit money banks (DBMs) in Nigeria for the period from 2007 to 2020.  The pre IFRS adoption period spanned from 2007 to 2011 while post adoption period spanned from 2012 to 2020.  The study adopted an ex-post facto research design because the study is purely secondary in nature. The population for the study consisted of all the 15 deposit money banks listed on the Nigerian Exchange Limited as at 31st December 2020, with a sample size of 12 banks. The Ohlson model was adopted for the study. Using ordinary least square regression, the study found out that post IFRS adoption model has more explanatory power than the pre IFRS adoption period.  Also, earning per share moderated by IFRS has a positive and significant effect on market price per share and book value per share moderated by IFRS has negative and significant effect on market price. The study concluded that earning per share is more value relevant with IFRS adoption of the listed deposit money banks in Nigeria while the value relevance of book value decreases with IFRS adoption of listed deposit money banks in Nigeria. The study recommended among others that prospective investors, shareholders, owners, and users of accounting data should place a greater emphasis on earnings per share, which has the strongest positive link with the market share price of listed DMBs in Nigeria